2017
DOI: 10.1038/s41598-017-03257-z
|View full text |Cite
|
Sign up to set email alerts
|

JNK Activation Turns on LPS- and Gram-Negative Bacteria-Induced NADPH Oxidase-Dependent Suicidal NETosis

Abstract: Neutrophils cast neutrophil extracellular traps (NETs) to ensnare microbial pathogens. Nevertheless, the molecular rheostats that regulate NETosis in response to bacteria are not clearly established. We hypothesized that stress-activated protein kinase or c-Jun N-terminal Kinase (SAPK/JNK) is a molecular switch that turns on NETosis in response to increasing concentrations of lipopolysaccharide (LPS)- and Gram-negative bacteria. Here we show that Escherichia coli LPS (0111:B4; 10–25 μg/ml), but not phorbol myr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
155
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(164 citation statements)
references
References 56 publications
6
155
1
2
Order By: Relevance
“…We utilized 25 nM PMA as an alternative stimulus for NETosis and were interested to find that PMA-induced NETs were completely ineffective for induction of Th17 cells (Supplementary Figure S2c), despite PMA being a strong stimulus for NETosis ( Supplementary Figures S2a, S2b). Recent studies (Khan et al, 2017) have shown that LPS and PMA utilize different signaling pathways to induce NETosis, with LPS triggering a Toll-like receptor 4edependent activation of nicotinamide adenine dinucleotide phosphate oxidase to effect NETosis (Khan et al, 2017). While both sets of experiments utilized E. coli 0111:B4 LPS, we used a much lower concentration (5 ng/ml vs. 100e25,000 ng/ml).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We utilized 25 nM PMA as an alternative stimulus for NETosis and were interested to find that PMA-induced NETs were completely ineffective for induction of Th17 cells (Supplementary Figure S2c), despite PMA being a strong stimulus for NETosis ( Supplementary Figures S2a, S2b). Recent studies (Khan et al, 2017) have shown that LPS and PMA utilize different signaling pathways to induce NETosis, with LPS triggering a Toll-like receptor 4edependent activation of nicotinamide adenine dinucleotide phosphate oxidase to effect NETosis (Khan et al, 2017). While both sets of experiments utilized E. coli 0111:B4 LPS, we used a much lower concentration (5 ng/ml vs. 100e25,000 ng/ml).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitation of DNA released from NETs revealed that treatment with 5 ng/ml LPS for 4 hours did not significantly increase NETosis (Supplementary Figure S2b). We also generated NETs using phorbol myristate acetate (PMA), another frequently used stimulus for NET formation (Khan et al, 2017). Interestingly, while 25 nM PMA was highly effective in inducing NETosis (Supplementary Figure S2b), the resulting NETs were completely ineffective in inducing Th17 cells (Supplementary Figure S2c).…”
Section: Nets Promote the Induction Of Th17 Cells From Pbmcmentioning
confidence: 99%
“…Having found an effect on NETosis, we next examined integrin activation and neutrophil adhesion, which are also implicated in NET release 34,35 . We measured neutrophil adhesion to primary human endothelial cells in the absence or presence of PMA (a general integrin activator) or lipopolysaccharide (LPS) (to mimic infectious stimuli), stimuli that activate NETosis via distinct pathways 36 . Hypoxia increased both unstimulated (23.6±4.0% vs 2.7±1.6%, p<0.05) and LPS-stimulated (35.7±4.8% vs 11.3±1.4%, p<0.05) adhesion to resting endothelium, whilst PMA-stimulated adhesion, which was already high, was unaffected (fig.…”
Section: Neutrophil Adhesion and Trans-endothelial Migration Are Enhamentioning
confidence: 99%
“…Immune complexes were found to drive NET formation through FcγRIIIb signalling, and opsonization of S. aureus with IgA induces the release of NETs through engagement of FcαR . NET formation requires the activity of mitogen‐activated protein kinases (MAPKs) . Recently, a number of other kinases have been linked to the formation of NETs in response to micro‐organisms, immune complexes and MSU crystals, such as spleen tyrosine kinase (SYK), phosphoinositide 3‐kinase (PI3K), IL‐1 receptor‐associated kinase (IRAK), PKC and AKT .…”
Section: Mechanisms Of Neutrophil Extracellular Trap Formationmentioning
confidence: 99%
“…60 NET formation requires the activity of mitogen-activated protein kinases (MAPKs). 61,62 Recently, a number of other kinases have been linked to the formation of NETs in response to micro-organisms, immune complexes and MSU crystals, such as spleen tyrosine kinase (SYK), phosphoinositide 3-kinase (PI3K), IL-1 receptorassociated kinase (IRAK), PKC and AKT. 18,55,59,[63][64][65][66] In line with the involvement of PI3K in NET release, studies have identified a role for autophagy, which also requires this signalling intermediate, in the formation of NETs.…”
Section: Signalling Pathwaysmentioning
confidence: 99%